ANALISIS SOFTWARE SISTEM INFORMASI PERPUSTAKAAN UNSLA VERSI 2.7 MELALUI PENDEKATAN TECHNOLOGY ACCETANCE MODEL (TAM) DI LINGKUNGAN UNIVERSITAS SEBELAS MARET SURAKARTA - Dian Hapsari (Ikatan Pustakawan Indonesia, 2015)
This study examines the usefulness and user acceptance as well as the ease and acceptance of users vho are using version 2.7 UNSLA in Sebelas Maret University Surakarta. In this study the authors used a quantitativ ? method that a study was conducted to determine one aspect of the research objectives widely used in data collecti In techniques although pegambilan samples. In quantitative research, the results may apply generally to all target areas of research. Results of the research that the usefulness factor (perceived usefulness) have significant positive effect on user acceptance (user acceptance) and usability factors (perceived ease of use) has a significant positivt efect on user acceptance (user acceptance). Thus, the library staff and library employees in the UNS believes that the information system useful for their work can affect the improvement of their acceptance of such systems.